The role of proteasome specific chaperones and quality control in assembly of the proteasome - Wani, Prashant Sadanand (Kansas State University, 2015)
The proteasome is a large protease in the cell that contributes to the controlled degradation of proteins. This 2.5MDa 26S proteasome complex consists of a 19S regulatory particle (RP) that recognizes substrates and a 20S proteolytic core particle (CP) that hydrolyses substrates. To function optimally all 66 subunits of the proteasome complex need to assemble properly. Efficient and accurate assembly of the proteasome is achieved with the help of proteins that can monitor the quality of the proteasome during pre- and post-assembly processes. The work in this thesis described an investigation into two of such quality control mechanisms. Pba1-Pba2 dimer has been known to facilitate the CP assembly by interacting with the top of the α-ring of CP throughout CP maturation. After CP maturation, RP utilizes same surface to form a CP-RP complex. Our data showed that Pba1-Pba2 binds tightly to the immature CP and prevents RP association. Once matured CP has a reduced affinity for Pba1-Pba2 and shows a higher affinity towards RP, resulting the formation of 26S proteasome complex. Our results imply that during maturation, CP undergoes conformational changes that results in this switch in affinity. Mathematical models indicate that during assembly such an 'affinity switch' quality control mechanism is required to prevent immature CP-RP complex formations. These types of wrong dead end products prevent efficient proteasome complex formation. Proteasomes formed with post-assembly defects are enriched with the proteasome associated protein Ecm29. Here Ecm29 is proposed to function as a quality control factor that inhibits such defective proteasomes to avoid aberrant protein degradation. This would require Ecm29 to preferably bind to mutant proteasomes. While we know Ecm29 interacts with RP as well as CP, we still don’t understand well how it binds to proteasomes holoenzyme. Here, we identify that besides the Rpt5 subunit of RP, Ecm29 binds to alpha7. We showed that conserved acidic residues containing unstructured C-terminal region of the CP subunit alpha7 facilitates the Ecm29-Proteasome interactions. Further mapping revealed the importance of phosphorylation of serine residues at the alpha7 C-terminal tail for Ecm29 interaction. We anticipate that this study leads to identification of specificity of the Ecm29 for the defective proteasomes. Overall this will help us to understand the role of Ecm29 in regulation of defective proteasomes in vivo.
Keywords: Proteasome; Chaperones; Quality control; Proteasome assembly; Biochemistry (0487); Cellular Biology (0379)